The Lady in White - Ruru, William (Te Kaharoa, 2020)
“Listen up youse fellas! I’m checking out that haunted house on Tui Street after school,” Pita ‘Poser’ Paraone announced to his classmates before their teacher Matua Tane arrived for the morning lesson. “Whose man enough to come with me?” he followed up quicky with his nose in the air.